Nutritional Status and Early Food Diversification in Infants Aged 200 Days in Three Municipalities of Abidjan - Mouroufie, A. K. J.; Aka, F. B. A.; Kouakou, F. K.; Coulibaly, N. D.; Kati-Coulibaly, S.; Faye-Kette, H.; Bosson, Y. V. E.; Djaman, L. Y. P. (European Journal of Applied Sciences, 2022)
It appears from this study that certain socio-demographic parameters influence the nutritional status of infants. The early introduction of foods greatly affects the nutritional status of children. For each manifestation of malnutrition, the prevalence is high among infants living in low socioeconomic households to infants in well-to-do households. This study shows that the majority of mothers are aged from 20 to 29 and 34% are pupils or students. Among them, 50% live in households with a high standard of living. Despite advice and recommendations on the practice of exclusive breastfeeding, 60% of infants started early food diversification between 0-119 days. The Height-for-Age (H/A) study indicates that among infants 21.6% have at-risk nutritional status, while 6.4% are stunted. The present study also indicates at the Weight/Height (W/T) level that among infants 26.9% have a nutritional status at risk and 3.3% are wasted. Regarding the weight-for-age (W/A) parameter, it appears that the proportion of children with a nutritional status at risk is 33.3% and 10.7% underweight. All infants who received early complementary foods are at risk of malnutrition.